Prevalence of Anxiety and Depression Among the Iraqi Repatriated Prisoners of the Iran-Iraq War, 1980-1988 - Al-Ameri, maan; gee, Ivan; Ma'ala, Eqbal; Wallymahmed, Akhtar (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To find out the prevalence of anxiety and depression among Iraqi repatriated prisoners of Iran-Iraq war(IRPOWs), and the relationship with some variables.Methodology: A descriptive study was carried out from Oct. 18th, 2009 through Jan. 10th, 2010. A Snowballsampling as a non-probability sampling technique was used to recruit 92 repatriates who had visited Ministry ofHuman Rights. An instrument was constructed for this purpose. The constructed instrument consisted of sixdemographic characteristics, and fourteen items to measure the level of anxiety and depression in prisoners ofwar (POWs). Data were collected with using the constructed instrument and the process of the interview as meansfor data collection. Data were analyzed through the application of descriptive statistical analysis, which are;percentages, frequencies and inferential statistic analysis (Pearson correlation coefficient).Results: The study revealed that the majority of IRPOWs have some levels of; anxiety (62.0%) with the levels of:mild (28.3%), moderate (25.0%), and severe (8.7%); and depression (63.0%) with the levels of: mild (27.2%),moderate (29.3%), and severe (6.5%). The findings also indicated that there is no significant relationship betweenanxiety and depression relative to; current age, age at capture, duration of captivity, marital status, and level ofeducation.Recommendations: The study recommends that it is very important to establish special mental health servicescentres within the primary health care centres deal with those repatriates for counselling and in order to diagnoseand treat them and further studies in this field with follow-up studies for the POWs